Announcement effects of dividend tax cuts and corporate policies: evidence from Malaysia REITs - Wong, Woei Chyuan; Taufil Mohd, Kamarun Nisham; Abdullah, Nur Adiana Hiau (Taylor & Francis Group, 2017)
This study examines the effect of dividend tax changes on the share prices and corporate policies of Malaysian REITs.Event study results show that dividend tax cut announcements provide positive abnormal returns.Based on cross-sectional regression, the abnormal returns are found to be larger for REITs with a higher retail ownership.The implementation of dividend tax cuts also increases dividend payout and reduce investment activities. These results partly support the traditional view of dividend taxation which posits that tax reform could affect economic efficiency and resource allocation in an economy